Advancements in cooling techniques for enhanced efficiency of solar photovoltaic panels: A detailed comprehensive review and innovative classification - Mohamad Abou Akrouch; Khaled Chahine; Jalal Faraj; Farouk Hachem; Cathy Castelain; Mahmoud Khaled (Energy and Built Environment)
Solar photovoltaic (PV) cells have emerged as the primary technology for producing green electricity. This innovation harnesses direct sunlight to generate power and its flexibility of installation has drawn significant investment in PV panels. Despite numerous benefits, these cells are hindered by a decline in efficiency caused by elevated cell temperature. As such, researchers have undertaken extensive investigations into possible solutions aimed at enhancing the performance of photovoltaic cells using diverse techniques. This review paper provides a thorough analysis of cooling techniques for photovoltaic panels. It encompasses both passive and active cooling methods, including water and air cooling, phase-change materials, and various diverse approaches. Within each category, it delves into detailed sub-categories, such as evaporative cooling, water immersion, floating systems, water pipes, cooling channels, water sprayers, jet impingement, geothermal cooling, and natural convection enhanced by PV designs. It also covers forced convection using cooling ducts, heat sinks, and air collectors, alongside the integration of Phase Change Materials (PCMs), nanofluids, radiative cooling, thermoelectric methods, heat pipes, heat pumps, and other innovative techniques. Each of these approaches is illustrated with specific schematics and thoroughly discussed and compared. Furthermore, this paper introduces an original classification system for these cooling methods applied to photovoltaic panels, offering valuable guidance for future research and insights into improving efficiency.